Optimalisasi Distribusi Surat Suara Pemilu pada Pemilihan Umum Serentak 2019 - Resista Vikaliana; I Nyoman Purnaya (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
The purpose of this study is to determine the process of ballot distribution and propose a model of the optimal ballot distribution process. This research is useful in providing input on the distribution of ballot papers for the first time this election is held simultaneously. The input is expected to increase effectiveness in the distribution or distribution of ballots so that they can produce good ballots when needed by the parties concerned. This study uses a qualitative approach with in-depth interviews with key informants, observation and documentation studies. The distribution model on the 2019 Simultaneous Election ballots is to be implemented in stages. For overseas distribution, in order to reduce distribution costs, enable digital signatures, and eVote, because the internet infrastructure is more adequate.